Diogenes Syndrome: A Case Report - Projna Biswas; Anusree Ganguly; Sanchaita Bala; Falguni Nag; Nidhi Choudhary; Sumit Sen (Hindawi Limited, 2013)
Cessation of normal skin cleansing seen in geriatric or self-neglected patients can cause accumulation of keratinous crusts on the skin. In the extreme end of this spectrum is a condition known as Diogenes syndrome (DS). These patients may have psychiatric disorders like paranoid disorders, mood affection, or temporofrontal dementia. Subjects are mainly the elderly but few cases in younger age group of patients have also been reported. Lesions of DS are usually found over upper central chest, back, and groin. In the young, lesions are mainly found over scalp, face, or arms. Absence of normal skin cleaning causes keratin and dirty debris to accumulate and with time form a thick shell. These debris can be secondarily infected by bacteria, fungus, and so forth. These skin lesions are not usually seen in individual with proper hygiene. We report a case of Diogenes syndrome in a 34-year-old young male patient who had associated schizophrenia.